A taxonomic study of the beetle cockroaches (Diploptera Saussure) from China, with notes on the genus and species worldwide (Blattodea: Blaberidae: Diplopterinae) - Li, Xinran; Wang, Zongqing (Zootaxa, 2015)
Four taxa of beetle cockroaches (Diploptera Saussure, 1864) from South China are described and illustrated, viz., two new species D. elliptica sp. n. and D. naevus sp. n., one new subspecies D. nigrescens guani subsp. n. and one widespread known species D. punctata (Eschscholtz, 1822). The genus and known species from around the world are discussed based on types and other specimens. D. pulchra Anisyutkin, 2007 is now regarded as a junior synonym of D. bicolor Hanitsch, 1925. Whether the populations of D. punctata represent or not different species needs to be studied in the future. A key, a distribution map, and photos of species are provided.